2017
DOI: 10.5539/ijbm.v12n4p111
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Transformational Leadership Behaviours on Organizational Commitment in Omani Governmental Organizations

Abstract: Public organizations all over the world have to confront renewed challenges and obstacles to meet citizens' needs. Indeed, Omani organizations are required to have leadership behaviours that clearly encourage and foster subordinates' performance by enhancing employees' commitment. The aim of this paper is to explore the influence of transformational leadership on organizational commitment in Omani public organizations. The quantitative data was collected through survey instrument. The current research utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…In other words, H1 in this study is supported. The results of the research are in agreement with the research of Al Zefeiti (2017) which states that organizational commitment influences organizational performance, where organizational commitment can be achieved if every individual in the organization has a dimension of Affective Commitment, Continuity Commitment, Normative Commitment to building high performance contextual.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In other words, H1 in this study is supported. The results of the research are in agreement with the research of Al Zefeiti (2017) which states that organizational commitment influences organizational performance, where organizational commitment can be achieved if every individual in the organization has a dimension of Affective Commitment, Continuity Commitment, Normative Commitment to building high performance contextual.…”
Section: Discussionsupporting
confidence: 88%
“…Currently, the challenge of performance enhancement in organizations has increased along with the struggle to manage the quality of the workplace, and accelerated competition among organizations, globalization, the rising expectation of citizens, all have led to organizations' aiming, mostly, on the quality within the contexts of the past few decades (Akdere, 2006in Al. Zefeiti 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, studies have found a positive relationship between organizational commitment and organizational performance (Suliman & Lles, 2000;Meyer et al, 2002). A committed employee is motivated to work better (Azeem, 2010;Al Zefeiti & Mohamad, 2017). The authors also state that a good work result will be obtained when employees have a strong motivation to work and a psychological attachment to the organization.…”
Section: Impact Of Employee Engagement On Organizational Commitment A...mentioning
confidence: 98%
“…Safety pandemic positively influences WFH culture. BIJ 30,4 4.4 Effect of organizational commitment on job demand Organizational commitment through affective dedication, normative dedication and continuance dedication motivates workers to engage themselves for the best interests of the organization (Al Zefeiti and Mohamad, 2017). Job demands may be described as the degree to which the operating surroundings consist of stimuli that require a few efforts (Jones and Fletcher, 1996).…”
Section: Safety Pandemic and Wfh Culturementioning
confidence: 99%